Obesity and morbid obesity associated with higher odds of hypoalbuminemia in adults without liver disease or renal failure - Mosli RH (Dove Medical Press, 2017)
Rana H Mosli,1 Hala H Mosli2 1Clinical Nutrition Department, Faculty of Applied Medical Sciences, King Abdulaziz University, Jeddah, Kingdom of Saudi Arabia; 2Division of Endocrinology and Metabolism, Department of Medicine, Faculty of Medicine, King Abdulaziz University, Jeddah, Kingdom of Saudi Arabia Background and objective: Studies are needed in order to inform recommendations for interpreting albumin levels among obese individuals without known medical conditions associated with hypoalbuminemia. The objective of this study was to examine the association of obese and morbidly obese status with hypoalbuminemia, while adjusting for age, sex, diabetes, prediabetes, diabetic nephropathy, and nephrotic syndrome.Patients and methods: Retrospective data collection from adult patients presenting to the outpatient Endocrinology and Metabolism Clinic was performed between January 2015 and December 2015. An initial sample of 180 patients was selected. After excluding patients who were younger than 18 years, who had known cases of liver disease or renal failure, or who had missing data, a final sample of 122 subjects was identified. Serum albumin and objectively measured weight and height data were retrieved from hospital records. A board-certified endocrinologist reviewed patient records to identify the presence of renal and diabetic conditions. Descriptive statistics were used to examine sample characteristics. Multiple logistic regression analysis was used to examine the association of obesity and morbid obesity with hypoalbuminemia (serum albumin < 34 g/L) while adjusting for age, sex, diabetes, prediabetes, diabetic nephropathy, and nephrotic syndrome.Results: Approximately 43% of the sample were categorized as obese and 13% were categorized as morbidly obese. The mean serum albumin level was 38.00 g/L (standard deviation [SD] = 4.26) among subjects who were neither overweight nor obese, 38.35 g/L (SD = 0.48) among overweight subjects, 34.57 g/L (SD = 4.71) among obese subjects, and 33.81 g/L (SD = 3.71) among morbidly obese subjects. Adjusting for age, sex, diabetes, prediabetes, nephrotic syndrome, and diabetic nephropathy, obese subjects had significantly higher odds of hypoalbuminemia (odds ratio [OR]: 4.10, 95% confidence interval [CI]: 1.50–11.27, P-value = 0.006), as did morbidly obese subjects (OR: 6.94, 95% CI: 1.91–25.23, P-value = 0.003).Conclusion: The findings suggest that obesity and morbid obesity can be considered as independent predictors of hypoalbuminemia. The findings can be used to inform future studies aiming to better understand the association of obesity and morbid obesity with hypoalbuminemia and to help inform guidelines for clinicians on how to correctly interpret and utilize serum albumin data for obese individuals. Keywords: obesity, morbid obesity, albumin, hypoalbuminemia, inflammation, diabetes mellitus